One-carbon metabolism and epigenetic programming of mammalian development - Clare, Constance E (2021)
One-carbon (1C) metabolism comprises a series of integrated metabolic pathways, including the linked methionine-folate cycles, that provide methyl groups for the synthesis of biomolecules and the epigenetic regulation of gene expression via chromatin methylation. Most of the research investigating the function of 1C metabolism pertains to studies undertaken in the rodent liver. Comparatively little is known about the function of 1C metabolism in reproductive and embryonic cells, particularly in domestic ruminant species. Periconceptional dietary deficiencies in 1C substrates and cofactors are known to lead to epigenetic alterations in DNA methylation in genes that regulate key developmental processes in the embryo. Such modifications can have negative implications on the subsequent development, metabolism and health of offspring. This thesis sought to improve current understanding of the regulation of 1C metabolism in the ruminant liver, ovary and preimplantation embryo through in vivo and in vitro nutritional supplementation experiments coupled with metabolomic, transcriptomic and epigenetic analyses.